Odnos študentk in študentov zdravstvene nege do homoseksualnosti - Lekše, Rebeka (Obzornik zdravstvene nege, 2022)
Introduction: Prejudice and discrimination against sexual minorities remain a widespread problem despite social changes. Homosexual individuals are exposed to strong negativism and violence, which has a detrimental effect on the psychological, physical and social health and well-being of individuals and the community. The purpose of the study was to research the attitudes of female and male nursing students towards homosexuality. Methods: A non-experimental quantitative descriptive research method was used. The research was conducted in December 2020 with a survey technique. The convenience sample included 114 undergraduate and postgraduate nursing students. Data were collected through the online Slovenian version of the questionnaire "Index of Attitudes towards Homosexuals". The internal consistency of the questionnaire was 0.94. Results: Half (56.1%) of the respondents know that an individual's gender identity characterizes their culture and is, therefore, a component of cultural competencies. 74.6% of them believe that they did not gain enough knowledge about this topic during their studies. The majority (86.8%) of students know someone who is gay. There are statistically significant differences in attitudes towards homosexuality among students, based on demographic and other data (p < 0.05). The most positive attitude towards homosexuality was shown by atheists, women, students aged 21 to 30 and second-year undergraduate students. Discussion and conclusion: Nursing students have a positive attitude towards homosexuality. It is necessary to include knowledge of cultural competencies in the study course.
Keywords: istospolna usmerjenost; izobraževanje; kulturne kompetence; percepcija; zdravstvena nega